Penerapan Strategi Picture Word Inductive Model dalam Menyusun Teks Deskriptif Berbahasa Inggris untuk Meningkatkan Prestasi Belajar Siswa Kelas VII-1 SMP Negeri 1 Brang Rea - Elmy Latifah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2021)
This study aims to improve the learning outcomes of grade VII-1 students of SMP Negeri 1 Brang Rea for the even semester of 2018/2019 in learning English, especially in describing certain objects, people, or places through the Picture Word Inductive Model learning strategy. The type of research used is Classroom Action Research (CAR), while the research subjects are 31-grade VII-1 students of SMP Negeri 1 Brang Rea in the even semester of the 2018/2019 academic year. Data collection is carried out simultaneously with observations during the action, while data analysis is carried out at the time of reflection of the action. From the results of the study, it was found that PWIM was significant in improving student learning outcomes in learning English, especially in describing certain objects/people/places for class VII-1 in the even semester of the 2018/2019 academic year. The pedagogical implication of this research is that the use of the PWIM strategy can help students explore many words and then arrange them into a paragraph and descriptive text in English. With pictures of certain objects/people/places, students get inspired by what words they will write to compose a descriptive text.